Pelayanan Pastoral Konseling Efektif Menurut Injil Yohanes 3:1-21 - Rezeki Gulo; Agus Mawarni Harefa; Yanuar Ada Zega (Sekolah Tinggi Pastoral Tahasak Danum Pambelum Keuskupan Palangkaraya, 2023)
The life of every God's people is never without serious problems, for example; skeptical of Christ, lack of self-knowledge as God's glorious creation, and doubts about his salvation. Referring to this problem, the writer conducts a theological analysis of the narrative of the Gospel of John. 3:1-21 as an alternative solution to the problem. The alternatives offered by this thought are: as God's people, they must experience spiritual renewal in the sense that they are born again, have integrity and an attitude of life as they are, understand the concept of salvation correctly, and respect themselves as God's precious creation. This study uses a qualitative method with a library approach. The final conclusion of the author about